Introgressions of Vitis rotundifolia Michx. to obtain grapevine genotypes with complex resistance to biotic and abiotic stresses - V. A. Volynkin; V. V. Likhovskoi; I. A. Vasylyk; N. A. Rybachenko; E. A. Lushchay; S. M. Gorislavets; V. A. Volodin; V. I. Risovannaya; E. K. Potokina (Вавиловский журнал генетики и селекции)
Vitis rotundifolia Michx. is one of the species of the family Vitaceae, with resistance to both biotic and abiotic stresses. The present study reports new scientific knowledge about the inheritance of resistance to downy mildew, powdery mildew and frost by V. vinifera varieties from V. rotundifolia. Recombinant lines of three hybrid populations from the crossing of the maternal genotype ♀M. 31-77-10 with V. rotundifolia hybrids were used as the object of the study. As a result of laboratory screening, more than 40 % of recombinants of the ♀M. 31-77-10× ×[DRX-M5-734+DRX-M5-753+DRX-M5-790] population showed a high degree of frost resistance (–24 °C), while 6 % of transgressive recombinants were characterized by a very high degree of resistance (–27 °С). The maternal genotype ♀M. 31-77-10 does not carry alleles of resistance to powdery mildew at the Run1 locus and in the field suffers from powdery mildew much more than the paternal genotypes. The prevalence of powdery mildew on vegetative organs in the three recombinant populations over the years varies on average between 3.2–17.1, 0.3–17.7 and 0.6–5.2 %, respectively. As a result, almost all recombinant genotypes that received a resistant allele from the paternal genome are highly resistant to powdery mildew.